2016
DOI: 10.15171/ijhpm.2016.48
|View full text |Cite
|
Sign up to set email alerts
|

Health Departments’ Engagement in Emergency Preparedness Activities: The Influence of Health Informatics Capacity

Abstract: Background: Local health departments (LHDs) operate in a complex and dynamic public health landscape, with changing demands on their emergency response capacities. Informatics capacities might play an instrumental role in aiding LHDs emergency preparedness. This study aimed to explore the extent to which LHDs' informatics capacities are associated with their activity level in emergency preparedness and to identify which health informatics capacities are associated with improved emergency preparedness. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…They found that only 1.3% of the workforce specialized in informatics and that limited training existed for those seeking such opportunities. Evidence published by Shah and colleagues [40] suggested that health Public Health, Population Health, and Epidemiology Informatics: Recent Research and Trends in the United States departments with a greater number of information systems were associated with greater activity level in emergency preparedness, including having developed or updated a written emergency plan; reviewed relevant legal authorities; participated in tabletop exercises or drills; participated in functional exercises or drills; participated in full-scale exercises or drills; assessed emergency preparedness competencies of staff; and provided emergency preparedness training of staff. The capacity to use information systems effectively likely predicts the ability to meet communication needs and gather and disseminate information.…”
Section: (2) Education and Workforce Developmentmentioning
confidence: 97%
“…They found that only 1.3% of the workforce specialized in informatics and that limited training existed for those seeking such opportunities. Evidence published by Shah and colleagues [40] suggested that health Public Health, Population Health, and Epidemiology Informatics: Recent Research and Trends in the United States departments with a greater number of information systems were associated with greater activity level in emergency preparedness, including having developed or updated a written emergency plan; reviewed relevant legal authorities; participated in tabletop exercises or drills; participated in functional exercises or drills; participated in full-scale exercises or drills; assessed emergency preparedness competencies of staff; and provided emergency preparedness training of staff. The capacity to use information systems effectively likely predicts the ability to meet communication needs and gather and disseminate information.…”
Section: (2) Education and Workforce Developmentmentioning
confidence: 97%
“…, 2020). As the “front-runner” of emergency response, Medical and Health Organizations (MHO), such as hospitals, grassroots medical and health institutions, and professional public health institutions, provide first-line medical care and basic public health services to victims who need emergency and urgent assistance during emergencies and disaster situations, including services crucial for minimizing harm from hazardous events (Shah et al. , 2016; Beyramijam et al.…”
Section: Introductionmentioning
confidence: 99%
“…The wide spread of the COVID-19 epidemic highlights the fragility of the global health and health system, especially the weak capacity for emergency preparedness and relief, as well as the limitations in the development of realtime response measures (Cao et al, 2020). As the "front-runner" of emergency response, Medical and Health Organizations (MHO), such as hospitals, grassroots medical and health institutions, and professional public health institutions, provide first-line medical care and basic public health services to victims who need emergency and urgent assistance during emergencies and disaster situations, including services crucial for minimizing harm from hazardous events (Shah et al, 2016;Beyramijam et al, 2020). Whether it is the threat posed by Emergency preparedness of MHO staff terrorism, climate change resulting in flooding, or a new virus for which there is no cure, they will be at the forefront of post-disaster intervention (Kim, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Health informatics is a combination of resources applied in the acquisition, storage, and retrieval of data to improve patient safety and quality of healthcare. The advent and integration of information technology systems has facilitated the identification of vulnerable individuals, which informs the emergency preparedness of the health care providers (Shah, Newell and Whitworth, 2016). Electronic health records provide a platform for collecting, analyzing, storing, and presenting healthcare information.…”
Section: Introductionmentioning
confidence: 99%